Analisis Penerapan Transaksi Murabah dalam Asuransi Syari’ah : Studi Kasus PT Bank Pembiayaan Rakyat Syari’ah (BPRS) Prima Medan - Atika, Atika; Anjelika, Melly (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Islamic Bank is a bank that refers to the procedures for the operation of the provisions of the Al-Qur’an and Al-Hadith as a source of  Islamic law. For the Indonesian economy, Islamic banks boom started in 1997 when the financial crisis occurred. Although Islamic banks have exsisted in Indonesia in 1992. Monetary crisis is a positive impact on the growth of Islamic banking in Indonesia because reality shows banks operating with Islamic principles can survive amid volatility in exchange and high interest at that time.The research was conducted at PT. BPR Syariah Gebu Prima Medan. The purpose of this study is to analiyze the suitability of the application of the system of financing Murabahah transactions PT. BPR Syariah Gebu Prima Medan and analyze the recognition and measurement of revenue murabahah transactions PT. BPR Syariah Gebu Prima Medan with PSAK 102. This research is descriptive qualitative. While the data source of primary data collected directly and secondary data obtained froms documents provided bye the company.From these results it can be concluded that the application of the system of financing murabahah transactions and income measurement murabahah transactins are implemented by PT. BPR Syariah Gebu Prima Medan in accordance with PSAK 102.